New Priorities for Dairy Cows Feed Production System Using Fuzzy-AHP - Prameswari, Puspa Ayu Indah (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 9, No. 3 December 2018DO - 10.24843/LKJITI.2018.v09.i03.p03, 2018)
Management criteria can be used as the deciding device of the performance of dairy cows feed production system successfulness by prioritizing those criteria, and it can be used as an improvement step. The aim of this study was to determine the priority of management criteria and established the improvement step to increase the performances of the dairy cows feed production system in Batu, East Java by prioritizing four management criteria (Planning, Organizing, Directing, and Controlling). The method used the Fuzzy Analytic Hierarchy Process (Fuzzy-AHP) which is a combination of two methods, Analytic Hierarchy Process (AHP) and fuzzy logic. Fuzzy AHP is proposing an evaluation tool which inherits advantages from that two methods. Fuzzy AHP will translate decisions makers comparison judgment into the fuzzy number. There were three highest priorities for management criteria, namely goal planning for the long-term from planning criteria, divisions of work from organizing criteria, and activator from controlling criteria. It was concluded that those three highest management criteria could be established as an improvement step for the performances of dairy cows feed production system.